Factors Associated with Hand Washing Practices Among Secondary School Students in Ndorwa East Constituency in Kabale District. - Twinomuhwezi, Benja (Kabale University, 2023)
Despite the world-wide Global Hand Washing Day campaign which targets school children as the most effective agents for behaviour change, there is limited documentation in various school settings. This study examined the factors associated with hand washing practices among secondary school students in Ndorwa east constituency. It was guided by two objectives; (i) to assess hand washing practices among secondary schools in Ndorwa East Constituency in Kabale district; (ii) to assess the factors associated with hand washing practices among the secondary school students in Ndorwa East Constituency. A cross-sectional study using quantitative method was conducted among 291 students from five schools. For qualitative data, the researcher used purposive sampling to identify 11 key informants (head teachers and teachers in charge of health and sanitation) and 48 participants in FGDs from the five schools. Systematic sampling was used to select students to participate in the study while simple random sampling was used to identify schools to participate in the study. Of the 291 respondents enrolled, 219(77%) washed their hands after the rest room. Factors associated with a higher likelihood of hand washing practice among secondary school students in Ndorwa East Constituency–Kabale District were being aged <18 years (aOR =8.1, 95%CI: 2.65-21.61, p<0.001), presence of water for hand washing(aOR =50.7,95%CI:11.50-309.38,p<0.001), presence of hand washing stations (aOR=7.3,95%CI:2.72-30.37, p<0.001), and cleanliness of hand washing stations (aOR=70.0,95%CI:10.44-605.6, p<0.001). The factors associated with hand washing practices were presence of water for hand washing, presence of hand washing stations in schools, cleanliness of hand washing stations. The study suggests that the school administrators should sensitize all students to continue practicing washing hands. This would help in preventing students from diseases associated with poor hand hygiene practices. Keywords: Factors, Hand Washing Practices, Secondary School Students, Ndorwa East Constituency, Kabale District.